Students' Scientific Literacy in Science Learning with SETS Vision Using the Problem Based Learning Model - Wijaya, Muhamad Effendi Satra; Rusilowati, Ani; Wardani, Sri (Educational Management, 2021)
This study aims to analyzed the improvement of students’ scientific literacy in science learning with SETS vision using the problem based learning model. This quasi experimental research with nonequivalent control group design. the sampling was done by purposive sampling technique, it was gained that grade IV-A students of Primary School 4 Aikmel as experimental class and grade IV-B students of Primary School 2 Aikmel as control class. The data colecting technique was test. Then, it was analyze by N-Gain test and the independent sample t-test. the results showed that there were differences improvement of students’ scientific literacy between the experimental class that implemented problem based learning model in science learning with SETS vision and the control class that implemented expository model. based on N-Gain test results, it shows that experimental class obtained improvement 0,46, categorized moderate, meanwhile, the control class obtained improvement 0.28, showing poor category. The improvement test results that analyzed by independent sample t test shows that the significant value obtained in the sig. (2-tailed) column is 0.001 < 0.05. It is means there was a significant improvement between students’ scientific literacy in experimental and control class